Environmental regulation, green innovation, and international competitiveness of manufacturing enterprises in China: From the perspective of heterogeneous regulatory tools. - Yuanhong Hu; Sheng Sun; Yixin Dai (PLoS ONE)
Based on combined data from the China Patent Database, China Industrial Enterprise Database, and China Customs Import and Export Database for the period 2004-2010, this study investigates the impact of heterogeneous environmental regulations on the export technological sophistication of manufacturing enterprises. Given deepening international market segmentation of production and the increasing proportion of intermediate trade, and compared with the traditional method based on exports, the export technological sophistication calculated here, based on value-added, is closer to the true level. Since there has been no in-depth comparative study on the relationship between heterogeneous environmental regulation and export technological sophistication, this study fills the gap. The results show that all three regulation types bear a U-shaped impact on export technological sophistication. Command-control regulation exhibits a restraining effect on mixed trade, eastern, and foreign-funded enterprises. Market-incentive regulation promotes processing and mixed trade enterprises as well as domestic and foreign-funded enterprises. Voluntary-participation regulation promotes all enterprises with different trade patterns and ownership. The mechanism analysis shows that command-control and market-participation environmental regulations affect export technological sophistication through the green invention and green utility innovation channels, while, additionally, market-incentive environmental regulation affects export technological sophistication through the green design innovation channel. Considering the environmental governance issues, the policy implications for enhancing the entire industrial chain and enterprises' export competitiveness are clear. Due to the unclear functions and powers of competent departments and a rigid threshold, command-control regulation is not conducive to cleaner production technology and the promotion of enterprises' export competitiveness; it should thus be discouraged. Although both market-incentive and voluntary-participation regulations have promoted cleaner production technology and enterprises' competitiveness significantly, the environmental tax system requires continuous improvement. The government should continue to raise public involvement in environmental protection to enrich the channels and forms of environmental management.